Optimizing Social Media Promotion Strategy to Increase Customer Retention Rate (CRR) with GKG Customer Engagement - Ifriza, Yahya Nur; Budiman, Kholiq; Ardiansyah, Adi Satrio (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2024)
In the digital age, businesses are increasingly relying on social media platforms to engage with their customers and foster brand loyalty. This paper presents a comprehensive study aimed at optimizing social media promotion strategies to enhance Customer Retention Rate (CRR) while utilizing the GKG (Get Keep Growth) Customer Engagement framework. By examining the interplay between social media promotion tactics and customer engagement metrics, we investigate how businesses can leverage data-driven insights to improve customer retention. Our research showcases the importance of tailoring social media campaigns to individual customer preferences and behavior, ultimately leading to increased customer satisfaction and loyalty. The results of the analysis of the development of the Customer Retention Rate graph were produced on FMIPA social media with an average CRR of 71% in the base case. Through a combination of data analysis and case studies, we provide actionable recommendations for businesses seeking to maximize the effectiveness of their social media promotion efforts and elevate their CRR with GKG customer engagement.